Experiências profissionais na escola e os sentidos da educação física - Loyola, Rosangela da Conceição (2009)
The current study aims at understanding in what way professional experiences make Physical Education a singular subject in the school context. We developed the research at a city school in Vitória-ES. In this sense, we searched for interaction spaces in which there were a greater number of experiences made by professionals. The approximation with the problem and the interpretations were based on the action theory. We chose a methodology of qualitative approach for the ethnographic study and for the participant observation. For so, we used as an instrument of data collecting the dialogs established with the professionals, the observation of spaces/interaction time, the analysis of the documents produced by the school. The subjects of the research were: the School Principal, the pedagogical professionals, the class teachers and the Physical Education instructors. As a result, we found four fundamental categories. Physical Education appears as a joker, a smaller subject, the Center of festivities and a place of great tension between professionalization and non-professionalization. The legitimacy of Physical Education into the Institution comes not for the recognition of its contents, but for the potential of support to the other subjects, its content and institutional organization. The representations built around Physical Education in this school cannot be abstracted from its specific knowledge, a fact that sometimes may not be noticed by professionals. In this conflicting game, Physical Education is sometimes in a way to be valued, sometimes in a way to be devalued as this devaluation tends to move through the school universe and although there was a certain meaning of appreciation of the subject in some punctual moments, sometimes fragile ones have occurred